Efficacy and Safety of Oral Herbal Drugs Used as Adjunctive Therapy for Melasma: A Systematic Review and Meta-Analysis of Randomised Controlled Trials. (6th December 2021) - Tang, Qingti; Yang, Hongjie; Liu, Xiarong; Zou, Yu; Lv, Xintong; Chen, Kai
Abstract : Background . Melasma is an acquired disorder of facial pigmentation. Its etiology is multifactorial; thus, the management is usually challenging. As a complementary therapy, herbal drugs are often used in the management of melasma. This work was aimed to investigate the efficacy and safety of herbal drugs on melasma in female patients. Methods . This study followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was conducted, and all randomised controlled trials (RCTs) on the use of oral herbal drugs as complementary therapy for melasma in female patients were included. A meta-analysis was conducted according to the guidelines of the Cochrane Collaboration using Review Manager 5.4. Results . Ten eligible trials, with 1015 female melasma patients, were included. All of the included RCTs had some concerns for risk of bias for different reasons, especially for that most of included trials were unblinded. Pooled data suggested phytotherapy plus routine therapy had significantly better efficacy on melasma than routine therapy, in terms of response rate (OR: 4.49, 95% CI: 3.25 to 6.20, p < 0.00001 ), reduction of skin lesion score (SMD: −0.56, 95% CI: −0.79 to −0.33, p < 0.00001 ), and improvement of serum E2 levels (SMD: −1.58, 95% CI: −2.62 to −0.55, p 0.003). In addition, there was no significant difference in the incidence of AEs between phytotherapy plus routine therapy and routine therapy (OR: 0.92, 95% CI: 0.53 to 1.58; p 0.76). Overall, herbal drugs used as an adjunct to routine therapy significantly enhanced the efficacy for the treatment of melasma but with a comparable safety profile. Conclusion . These findings have implications for recommending herbal drugs as a viable complementary treatment option for melasma.